Effect of Acid Catalysts on CO2 Absorption Process by Mixed Amines. (July 2017) - Srisang, Wayuta; Osei, Priscilla Anima; Decardi-Nelson, Benjamin; Tontiwachwuthikul, Ananda Akachuku Paitoon; Idem, Raphael
Abstract: This study evaluated the effects of two solid acid catalysts (γ-Al2 O3 and HZSM-5), and two tertiary amines (methyldiethanolamine and 4-(diethylamine)-2-butanol mixed with monoethanolamine on the CO2 capture process performance in terms of heat duty, cyclic capacity and absorber efficiency using a bench scale amine-based post-combustion CO2 capture pilot plant with different amounts of each solid acid catalyst in the desorber. Comparisons were made between 5 M MEA, 5 M MEA/2 M MDEA, and 5 M MEA/1.25 M DEAB with and without catalyst in the desorber. It was found that 5 M MEA/1.25 M DEAB with HZSM-5 gave the highest cyclic capacity, absorption efficiency and lowest heat duty.